2001
DOI: 10.11609/jott.zpj.16.5.493
|View full text |Cite
|
Sign up to set email alerts
|

First record of a nemopterid (Neuroptera: Nemopteridae) from Maharashtra

Abstract: During the course of faunistic survey of Tadoba-Andhari Tiger Reserve, Chandrapur District, Maharashtra in April 2000, we encountered altogether five specimens of Croce filipennis Westwood, a member of family Nemopteridae of order Neuroptera. Again one of us (SST) could collect a single specimen of the same species from Lakhani Village, Bhandara District, Maharashtra (approximately 150 km. away from Tadoba) on 27 April 2000. Earlier, in 1998 we had collected a single mutilated specimen of the same species from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The present specimens have also been spotted in the month of March. Some other reports also con rms the seasonal appearance of the species in its habitat (Khot and Patil 2011; Rajasekar and Sridevi 2018; Sharma et al 2001).…”
Section: Discussionmentioning
confidence: 66%
“…The present specimens have also been spotted in the month of March. Some other reports also con rms the seasonal appearance of the species in its habitat (Khot and Patil 2011; Rajasekar and Sridevi 2018; Sharma et al 2001).…”
Section: Discussionmentioning
confidence: 66%
“…The results for this study agree with those of Sliva and Grunewald [30], who indicated the laciniae of Lutzomyia migonei (Diptera) serves to feed on other insect hosts, and these mouthparts appear suitable for hooking into soft skin. Sharma et al [8] reported that the Neuroptera order contains numerous predaceous insects that feed on soft-bodied insects, including pests. Therefore, this order warrants further study.…”
Section: Mouthpart Morphologymentioning
confidence: 99%
“…Sole et al [6] studied the molecular phylogeny of the South African Nemopteridae genera, and a new species of the Nemopteridae family was recently reported in Chile [7]. Most of these insects are plant-feeding, although some are predators [8,9]. Both groups are considered beneficial for maintaining a healthy ecosystem: plant-feeding nemopterids primarily aid with pollination, whereas predatory nemopterids participate in biological control.…”
Section: Introductionmentioning
confidence: 99%